Prevalence of Unruptured Intracranial Aneurysm on MR Angiography - Jeon, Tae Yeon (The Korean Society of Radiology, 2011)
OBJECTIVE: To evaluate the prevalence of incidentally found unruptured intracranial aneurysms (UIAs) on the brain MR angiography (MRA) from a community-based general hospital. MATERIALS AND METHODS: This was a prospectively collected retrospective study, carried out from January 2004 to December 2004. The subjects included 3049 persons from a community-based hospital in whom MRA was performed according to a standardized protocol in an outpatient setting. Age- and sex-specific prevalence of UIAs was calculated. The results by MRA were compared with intra-arterial digital subtraction angiography (DSA) findings. RESULTS: Unruptured intracranial aneurysms were found in 137 (5%) of the 3049 patients (M:F = 43:94; mean age, 60.2 years). The prevalence of UIAs was 5% (n = 94) in women and 4% (n = 43) in men, respectively (p = 0.2046) and showed no age-related increase. The most common site of aneurysm was at the distal internal carotid artery (n = 64, 39%), followed by the middle cerebral artery (n = 40, 24%). In total, 99% of aneurysms measured less than 12 mm, and 93% of aneurysms measured less than 7 mm. Direct comparisons between MRA and DSA were available in 70 patients with 83 UIAs; the results revealed two false positive and two false negative results. CONCLUSION: This community-hospital based study suggested a higher prevalence of UIAs observed by MRA than previously reported. These findings should be anticipated in the design and use of neuroimaging in clinical practice.